2022
DOI: 10.1017/s1755048322000062
|View full text |Cite
|
Sign up to set email alerts
|

Similar yet not the Same: Right-Wing Populist Parties' Stances on Religion in Germany and the Netherlands

Abstract: Applying a qualitative framing analysis, this paper examines narratives of the right-wing populist parties Alternative for Germany (AfD) and the Party for Freedom (PVV) in the Netherlands on religion. The paper argues that references of these populist parties to religion can be interpreted against the background of specific national context factors such as the respective history of nation building, the traditional role of religion in society and secularization processes. A rigorous examination of parliamentary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Besides providing an empirical analysis, Beuter and Kortmann (2022) also deliver an explanation for the differences between the two countries turning to the specific national context factors. Germany presents a particular case due to the belated German nation-building, the horrific national socialist history, and the subsequent division of the country.…”
Section: Country Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides providing an empirical analysis, Beuter and Kortmann (2022) also deliver an explanation for the differences between the two countries turning to the specific national context factors. Germany presents a particular case due to the belated German nation-building, the horrific national socialist history, and the subsequent division of the country.…”
Section: Country Examplesmentioning
confidence: 99%
“…In their comparative article, Beuter and Kortmann (2022) examine parliamentary documents from Germany and the Netherlands between October 2017 and December 2019, analyzing how the German populist party Alternative for Germany (AfD) and the Dutch Party for Freedom (PVV) refer to religion. The authors find that the self-other antagonism typically found in populist parties can also be found when the AfD and PVV refer to Islam and Christianity.…”
Section: Country Examplesmentioning
confidence: 99%